Enhancing Financial Statement Quality With Blockchain Technology - Azzoune, Nabila; Meghdouri ,Chahrazed (جامعة الوادي University of Eloued, 2024)
This study examines how blockchain can be linked to financial statements, including the income statement, balance sheet, statement of changes in equity, and statement of cash flows. The study sample included banks, financial institutions, and stock exchange intermediaries in Algeria. The results showed that factors such as security, privacy, transparency, auditability, immutability, cost reduction, real-time transactions, and flexibility are likely to influence the adoption of blockchain technology, which can have a positive impact on financial performance and competitive advantage for banks.
Keywords: blockchain; financial statements; audit; Distributed Ledger Technology